The Effect of Aromatherapy (Peppermint, Lavender, Green Tea, Lemon, Cinnamon) on the Reduction of Dysmenorrhea Pain in Women of Reproductive Age - Dyah Mayasari Fatwa; Fiki Retiasih; Maulidiana Khasanah; Vera Atikah; Winda Ristriana Putri; Yuli Nur Latifah (Jurnal Penelitian Pendidikan IPA, 2025)
Dysmenorrhea, characterized by painful menstrual cramps, is a common condition among women of reproductive age that often disrupts daily activities and overall quality of life. Aromatherapy, as a complementary and non-pharmacological approach, has been proposed to alleviate such pain through its physiological and psychological effects. This study aimed to determine the effectiveness of peppermint, lavender, green tea, lemon, and cinnamon aromatherapy in reducing dysmenorrhea pain among women of reproductive age. A quasi-experimental design with a pre-test and post-test control group approach was employed. A total of 75 respondents were recruited and randomly assigned to the intervention group (n = 38) and the control group (n = 37). The intervention group received aromatherapy using selected essential oils during menstruation, while the control group received no treatment. Pain intensity was assessed using a standardized numerical rating scale (NRS). Data were analyzed using paired t-tests and multivariate analysis to compare pre- and post-intervention pain levels between groups. The findings demonstrated a significant decrease in dysmenorrhea pain levels in the intervention group compared to the control group (p < 0.001). The mean pain score in the intervention group decreased from 7.8 ± 1.2 to 3.2 ± 1.1, while in the control group it only declined from 7.6 ± 1.3 to 6.5 ± 1.4. The observed reduction in pain supports the analgesic and relaxation properties of essential oils, particularly through their influence on the central nervous system and hormonal balance. These findings align with previous studies suggesting that aromatherapy may enhance endorphin release and reduce muscle tension associated with dysmenorrhea. Aromatherapy using peppermint, lavender, green tea, lemon, and cinnamon essential oils is effective as a complementary therapy for reducing dysmenorrhea pain in women of reproductive age. This non-pharmacological approach can be recommended as an accessible and safe alternative to improve menstrual health and comfort.